2020
DOI: 10.1002/hep.31067
|View full text |Cite
|
Sign up to set email alerts
|

The Spectrum of Reactive Cholangiocytes in Primary Sclerosing Cholangitis

Abstract: Cholangiocytes are the target of a group of chronic liver diseases termed the “cholangiopathies,” in which cholangiocytes react to exogenous and endogenous insults, leading to disease initiation and progression. In primary sclerosing cholangitis (PSC), the focus of this review, the cholangiocyte response to genetic or environmental insults can lead to a heterogeneous response; that is, a subpopulation acquires a ductular reactive and proliferative phenotype, while another subpopulation undergoes senescence and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 46 publications
2
34
0
Order By: Relevance
“…Together, our data support that EVs are an essential component of the cholangiocyte SASP. Our findings also suggest that EVs from senescent cholangiocytes may influence both the proliferative cholangiocyte niche (ie ductular reactive), at least in part through EGFR activation, as well as promote nonproliferative, senescent niche, both of which are implicated in the pathogenesis of cholestatic disease 5 . We further demonstrate that target malignant cholangiocyte proliferation and migration are enhanced by senescent cholangiocyte EVs, again through an EGFR‐dependent manner.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Together, our data support that EVs are an essential component of the cholangiocyte SASP. Our findings also suggest that EVs from senescent cholangiocytes may influence both the proliferative cholangiocyte niche (ie ductular reactive), at least in part through EGFR activation, as well as promote nonproliferative, senescent niche, both of which are implicated in the pathogenesis of cholestatic disease 5 . We further demonstrate that target malignant cholangiocyte proliferation and migration are enhanced by senescent cholangiocyte EVs, again through an EGFR‐dependent manner.…”
Section: Discussionsupporting
confidence: 65%
“…The cholangiocyte (biliary epithelia) response to injurious stimuli plays a critical role in initiating, modulating and exacerbating PSC disease progression 4,5 . We have previously shown that senescent cholangiocytes are abundant in livers of patients with PSC 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…In fact, cholangiocytes seem to respond to endogenous or exogenous insults by acquiring the ability to proliferate and secrete different pro-inflammatory mediators acting in a paracrine and/or autocrine manner. This determines the recruitment and stimulation of immune cells and fibroblasts, which induce the development of the typical PSC fibro-inflammatory lesions [4,5]. In case of persisting chronic injury, the reparative process becomes ineffective, and the inflammatory response perseveres, promoting ductular reaction (DR) and inducing cellular senescence (CS) J o u r n a l P r e -p r o o f in chronic injured cholangiocytes [4,5].…”
Section: Highlightsmentioning
confidence: 99%
“…This determines the recruitment and stimulation of immune cells and fibroblasts, which induce the development of the typical PSC fibro-inflammatory lesions [4,5]. In case of persisting chronic injury, the reparative process becomes ineffective, and the inflammatory response perseveres, promoting ductular reaction (DR) and inducing cellular senescence (CS) J o u r n a l P r e -p r o o f in chronic injured cholangiocytes [4,5]. CS is a cell state triggered by stressful insults and certain physiological processes, characterized by a prolonged and generally irreversible cellcycle arrest in the G 1 phase, associated to the acquisition of secretory features, the so-called senescence-associated secretory phenotype (SASP), macromolecular damage, and altered metabolism [6].…”
Section: Highlightsmentioning
confidence: 99%
“…2e5 PSC is a liver disease (more frequent in middle-aged men) 4 that targets extrahepatic and/or intrahepatic bile ducts and is characterized by biliary strictures and activation of hepatic stellate cells (HSCs), causing excessive collagen deposition. 2,3,6,7 PSC phenotypes can also progress to severe disorders, such as cholangiocarcinoma and pancreatic and colorectal cancer. 4 There is growing evidence that during the progression of cholangiopathies, cholangiocytes undergo cellular senescence, thereby secreting several cytokines (ie, senescence-associated secretory phenotypes), including transforming growth factor-b1 (TGF-b1), IL-6, IL-8, C-C motif chemokine ligand 2, and plasminogen activator inhibitor-1, which trigger activation of HSCs by paracrine mechanisms.…”
mentioning
confidence: 99%